Fertigasi Pada Hidroponik Wick Dengan Pupuk Organik Cair Kotoran Sapi Untuk Tanaman Cabai - Renaldy S Mamangkey; Dedie Tooy; Daniel P. M. Ludong (JURNAL BIOS LOGOS, 2023)
Chili (Capsicum annum L.) is a type of vegetable that is widely cultivated by farmers in several regions in Indonesia. The productivity of chili plants has decreased due to the excessive use of inorganic fertilizers. Fertilization using liquid organic fertilizer from cow dung is one effort to minimize the use of inorganic fertilizers. This study aims to examine the application of POC nutrition from cow dung in a wick hydroponic fertigation system for the development of chili plants. Observations were made to determine the water needs of plants (evapotranspiration) and the development of hydroponic chili plants with different concentrations of nutrients from liquid organic fertilizer from cow dung. Optimal treatment of giving nutrient concentrations of cow dung liquid organic fertilizer to plant water needs or evapotranspiration and development of chili plants is found at a concentration of 1,000 ppm (P3).